1974
DOI: 10.1021/ba-1974-0132.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Hydroformylation with Rhodium-Amine Complexes

Abstract: Under mild conditions, hydroformylation of olefins with rhodium carbonyl complexes selectively produces aldehydes.A one-step synthesis of oxo alcohols is possible using monomeric or polymeric amines, such as dimethylbenzylamine or anion exchange resin analog to hydrogenate the aldehyde. The rate of aldehyde hydrogenation passes through a maximum as amine basicity and concentration increase. IR data of the reaction reveal that anionic rhodium carbonyl clusters, normally absent, are formed on addition of amine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…These results are in line with the conclusions of Whitehurst et al who have shown that rhodium/amine complexes catalyze hydrohydroxymethylation of 1-hexene for amines of pKa between 7 and 11. 14 No alcohol was found with very weak or very strong nitrogen compounds in terms of pKa. Therefore, the basicity of the ligand is a key factor to obtain alcohols.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results are in line with the conclusions of Whitehurst et al who have shown that rhodium/amine complexes catalyze hydrohydroxymethylation of 1-hexene for amines of pKa between 7 and 11. 14 No alcohol was found with very weak or very strong nitrogen compounds in terms of pKa. Therefore, the basicity of the ligand is a key factor to obtain alcohols.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This behavior was probably due to the low pKa value. Indeed, some works relative of the HHM of olefins showed that the rhodium/amine complexes were only efficient to produce alcohols for pKa values comprised between 7 and 11 [ 29 ]. The other tested amines met this requirement.…”
Section: Resultsmentioning
confidence: 99%
“…The process in a one-step reaction with a single catalyst is the best alternative, owing to the reduction in the amount of the catalyst, the reaction time, and the overall cost. In this context, one of the best systems is a Rh-catalyst associated with tertiary amines in the presence of CO/H 2 [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In this publication, we report the HHM of isosorbide diallyl ether using this catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…Highpressure IR spectroscopy supports this explanation as the same unidentified rhodium species observed with [RhH(CO)(PPh 3 ) 3 ] is detected. 94 An effect on regioselectivity opposite to that of phosphines has been reported for the same general structure [RhX(CO)2L]. Little attention has been paid to the use of nitrogen-containing ligands.…”
Section: (/) Cobalt Compoundsmentioning
confidence: 99%
“…Only one 77-alkene complex exists for each diastereomer, but two allowed conformations (91) and (92) 97 The strong inhibiting effect of CO pressure indicates that the rate-determining step is the formation of [RuH 2 (CO)2(PPh 3 )2] (96), which follows dissociation of a carbonyl ligand from (94). Only one 77-alkene complex exists for each diastereomer, but two allowed conformations (91) and (92) 97 The strong inhibiting effect of CO pressure indicates that the rate-determining step is the formation of [RuH 2 (CO)2(PPh 3 )2] (96), which follows dissociation of a carbonyl ligand from (94).…”
Section: (R)mentioning
confidence: 99%